Integration and simulation of solar energy with hot flue gas system for the district cooling application - Inayat, A. (Elsevier Ltd, 2020)
The worldwide cooling demands are rising drastically. Several causes lead to this scenario such as industrialization, global warming and tropical climate region. This prompts the application of district energy such as district cooling system to fulfill the demands utilizing solar energy for cooling. Hybrid energy systems are sustainable and able to enhance the overall efficiency of the system. The current study provides the feasibility of solar cooling system integrated with the hot flue gases to produce chilled water, which can be scale up later for solar district cooling application. The parametric study conducted by using TRNSYS software to examine the feasibility and potential of integrated solar absorption cooling system. The simulation has been carried out using the feasible parameters of flat plate collector with 5Â° of collector slope, 15 m2 collector area, and 0.8 m2 tank size for thermal energy storage. The feasibility of the system investigated with respect to the cooling demand of a particular modeled building. It predicted that the room temperature of the building model is lower after the application of the solar cooling system. The case study conducted and simulated based on the weather for Kuala Lumpur, Malaysia. Â© 2020 The Authors.